A systematic review and meta‐analysis of the impact of lymphovascular invasion in bladder cancer transurethral resection specimens. (29th June 2018) - Mari, Andrea; Kimura, Shoji; Foerster, Beat; Abufaraj, Mohammad; D'Andrea, David; Hassler, Melanie; Minervini, Andrea; Rouprêt, Morgan; Babjuk, Marko; Shariat, Shahrokh F.
Abstract : The aim of the present review was to assess the prognostic impact of lymphovascular invasion (LVI) in transurethral resection (TUR) of bladder cancer (BCa) specimens on clinical outcomes. A systematic review and meta‐analysis of the available literature from the past 10 years was performed using MEDLINE, EMBASE and Cochrane library in August 2017. The protocol for this systematic review was registered on PROSPERO (Central Registration Depository: CRD42018084876) and is available in full on the University of York website. Overall, 33 studies (including 6194 patients) evaluating the presence of LVI at TUR were retrieved. LVI was detected in 17.3% of TUR specimens. In 19 studies, including 2941 patients with ≤cT1 stage only, LVI was detected in 15% of specimens. In patients with ≤cT1 stage, LVI at TUR of the bladder tumour (TURBT) was a significant prognostic factor for disease recurrence (pooled hazard ratio [HR] 1.97, 95% CI: 1.47–2.62) and progression (pooled HR 2.95, 95% CI: 2.11–4.13), without heterogeneity ( I 2 = 0.0%, P = 0.84 and I 2 = 0.0%, P = 0.93, respectively). For patients with cT1–2 disease, LVI was significantly associated with upstaging at time of radical cystectomy (pooled odds ratio 2.39, 95% CI: 1.45–3.96), with heterogeneity among studies ( I 2 = 53.6%, P = 0.044). LVI at TURBT is a robust prognostic factor of disease recurrence and progression in non‐muscle invasive BCa. Furthermore, LVI has a strong impact on upstaging in patients with organ‐confined disease. The assessment of LVI should be standardized, reported, and considered for inclusion in the TNM classification system, helping clinicians in decision‐making and patient counselling.